Time to return to school in child and adolescent burn for patients from a sub-saharan tertiary hospital (2019)
Background: Africa, with the largest number of paediatric burns needs to focus more attention on paediatric burn survivors. Burn injury truncates schooling in child and adolescent burn patients. The aim of this study was to determine the time to return to school and factors influencing this in child and adolescent burn patients. Methodology: A cross-sectional study of child and adolescent patients aged one to nineteen years that had been managed for bun injuries. Demographic variables were obtained from archived computerized data. Phone interviews were conducted to obtain time to return to school variables using a questionnaire. Descriptive statistics, students t test, fishers exact test and Chi square test were uses as appropriate for analysis on data on SPSS version 23. A p value <0.05 was considered statistically significant. Results: Thirty-one patients were recruited for the study. There was a female preponderance, 19 (61.3%). The mean age of the patients was 7.2 (±5.3) years. Scald injuries were the commonest [N = 14 (45.2%)] cause of burn. The mean Total Burn Surface Area (TBSA) was 14.1 (±12.0)%. The mean length of hospital stay was 30 (±59) days. The mean time to return to school after discharge from the hospital was 8.4 (±8.7) weeks. The occurrence of burns on the trunk was significantly (p = 0.048) associated with an earlier time to return to school. Conclusion: Time to return to school from burn injury and from discharge in child and adolescent burn survivors in this study are at least three times longer than previous studies. The burn care team needs to consider school re-entry programs for these children.